ANALISA SENTIMEN REVIEW PRODUK HANDPHONE PADA SITUS AMAZON MENGGUNAKAN PENDEKATAN LEXICON BERDASARKAN SENTIWORDNET - Anugerah Tri Siswanto; Rani Rotul Muhima; Septiyawan Rosetya Wardhana (Institut Teknologi Adhi Tama Surabaya, 2022)
Sentiment analysis is part of opinion mining, is the process of understanding, extracting and processing textual data automatically to obtain information. It is done to find out the attitude of a speaker or writer later to be classified into positive or negative sentiment groups. In this study, the determination of the word value in the document is determined using Lexicon Sentiwordnet as a benchmark for word value, the review document will go through several pre-processing stages including Delete URLs, Remove Punctuation, Casefolding, Delete Stopwords, POS Tagging, Sentence tokens, and tokens. word so that the review document data are structured. Furthermore, the Sentiwordnet Interpretation calculation is carried out to determine the value of a term or word in the document to determine whether the word is a positive or negative word based on its category in the POS Tagging process. Then do the calculation of the term score summation, calculate the value of the sentence, calculate the text score, and the results of the rating system that will generate a rating to determine the quality of a mobile phone product based on user reviews.